2004
DOI: 10.1088/0022-3727/37/14/020
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the weakest-link model for early electromigration failure

Abstract: The application of the weakest-link or failure-unit model to electromigration failure is discussed in relation to a simple model that should describe the early failures in fine-line, as-patterned aluminium reasonably well. The earliest failures are expected to be due to the presence of at least one polygranular cluster longer than some critical (Blech) length, while the next earliest are assumed to arise from linked shorter clusters. Using a simple model of the microstructure, the probability density function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…However, it has been shown that the failure-unit model does not fit comfortably with EM failure. 16 The main problems being ͑i͒ a sensible definition of what should constitute a failure unit and ͑ii͒ the sense in which such units would behave independently-a necessary requirement of the model.…”
Section: B Arguments Based On Failure Unitsmentioning
confidence: 99%
“…However, it has been shown that the failure-unit model does not fit comfortably with EM failure. 16 The main problems being ͑i͒ a sensible definition of what should constitute a failure unit and ͑ii͒ the sense in which such units would behave independently-a necessary requirement of the model.…”
Section: B Arguments Based On Failure Unitsmentioning
confidence: 99%